An Exploration of Leadership Characteristics in College Athletes - Eiche, Keith; Sedlacek, William; Adams-Gaston, Javaune (My University, 1999)
Research has been unclear as to what is associated with being a student athlete with leadership qualities. The purpose of this study was to provide more descriptive information regarding the attitudes and behaviors associated with leadership qualities in university athletes. The participants were 73 freshman athletes at a large mid-Atlantic research university with a NCAA Division I athletic program. Participants were recruited from freshman orientation to college classes that are offered to assist incoming freshmen with adjusting to college life. The data suggested that leadership in university athletes is associated with: expecting higher grades, certainty of college major, decreased need for emotional/social counseling, increased social adjustment, and lower expectancy for transferring to another university. These results are discussed in terms of advising issues for student athletes. Leadership in athletes was associated not only with graduating with a degree but higher leadership scores were associated with wanting to obtain a graduate degree. Leadership in college athletes appears to be associated with a strong internal sense of control and an optimism when dealing with problems. Athletes are certainly placed in situations where they can develop their leadership skills, and these situations may draw out leadership behaviors in individuals who may not otherwise exhibit such characteristics.
Keywords: skills; freshmen; transitions